Awareness of new payment technologies in the digital banking transformation - Accelerated by the COVID 19 pandemia - Torres, Nuno Miguel Silva (2022)
Dissertation presented as the partial requirement for obtaining a Master's degree in Statistics and Information Management, specialization in Risk Analysis and Management